The fiscal costs of financial instability revisited - Felix Eschenbach; Ludger Schuknecht (European Central Bank (ECB), 2002)
This paper conducts a comprehensive analysis of the fiscal costs of financial instability (defined as major asset price changes and including, as extreme cases, financial crises). The study identifies three channels to fiscal accounts: 1) revenue effects on capital gains, asset turnover and consumption tax, 2) bailout costs as asset price declines undermine balance sheets of companies/banks, and 3) second-round effects from asset prices changes via the real economy and via debt service costs. A panel analysis and case studies show that episodes of financial instability increase the variability of fiscal balances. Moreover, fiscal costs are often very large and much larger than assumed in the literature so far with public debt rising by up to 50% of GDP during such episodes. These fiscal effects can also serve as a, so far under-emphasised, rationale for the deficit and debt targets in the EU's Maastricht Treaty and Stability and Growth Pact.
Keywords: H3; H6; E6; 330; asset prices; deficits; financial crisis; financial stability; Fiscal policies